Pelaksanaan Media Pembelajaran Audio Visual Barbasis MP4 Dalam Meningkatkan Semangat Menghafal Al Quran Santri Madrasah Aliyah Di Pesantren Imam Muslim Kabupaten Serdang Bedagai - Ansari, Imam; Nasution, Rusli Halil; Novianti, Winda (STAI Tebing Tinggi Deli, 2024)
There are many methods and media that can be utilized in learning activities including memorizing the Qur'an. This study will focus on the application of methods and media utilized in memorizing the Qur'an. One of the media used is audio-visual media. The use of media in learning is believed to have a very good impact, but in memorizing the Qur'an it is still rarely used. The problems in this study are: 1. How is the implementation of the audio-visual learning method in improving the ability of students to memorize the Qur'an at the Imam Muslim Islamic boarding school 2) How to improve the ability of students to face the Qur'an at the Imam Muslim Islamic boarding school. The purpose of this study was to analyze the improvement of memorization skills using audio-visual media, and to see how students participate in using audio-visual media. To solve the above problems, an experimental research method was used with a pre-experimental design research design through a one group pretest-posttest design approach. The data in this study were collected through test and questionnaire techniques. The results showed that there was a significant influence in the application of the memorization method using audio-visual. While the response of students in the use of audio visuals can bargain well So, it can be concluded that the application of memorization methods through audio visuals can improve memorization skills at the Imam Muslim Islamic boarding school